Investigating Intention-to-Use Sharia Financial Technology in New Normal Era - Eri Puspita, Rosana; Puput Yanita Senja; Imanda Firmantyas Putri Pertiwi (International Journal of Islamic Business and Economics (IJIBEC), 2020)
The new normal era has made the digital-based industries have better prospects, including the Sharia fintech industry. This study investigates the influence of knowledge on product, attitude, and intention-to-use related to the Sharia Financial Technology. This study three variables consisting of knowledge on product, attitude, and intention. A quantitative approach was used in this research with a regression test. The data were collected using an online survey of 60 respondents. The results indicated that knowledge on Sharia Fintech affects attitude and intention-to-use Sharia Fintech. The knowledge on product provided a significant influence to shape attitude and intention. Not many studies were conducted on the new normal conditions, including the Sharia fintech industry. For practitioners, this research is possibly useful as a reference to map the Muslim markets in the fintech industry. This study highlighted the importance of fintech in the new normal era to reduce the spread of covid-19 virus